Beginning Adobe AIR : building applications for the Adobe Integrated Runtime - Tretola, Rich, 1971- (Wrox beginning guides., 2008)
Beginning Adobe AIR. Adobe Integrated Runtime (AIR) is revolutionizing the way desktop applications are deployed. If you're ready to take advantage of this platform to build desktop-based Rich Internet Applications, then this is the book for you. It presents a step-by-step process, walking you through the features of AIR so you can quickly get started. After introducing you to AIR, Adobe expert Rich Tretola discusses the different programming languages and tools you can use for development. He then presents multiple methods for storing data, including within the file system and embedded databa.